THE CONCEPT OF WORKING CONDITIONS AND GENERAL RULES OF ITS CHANGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the concept of working conditions in labor relations and the legal basis for its change, as well as its role and peculiarities in the regulation of labor relations.